Cultura organizacional y satisfacción laboral en la Empresa Pública Aguas de Manta - Alcívar Intriago, María Elena (2024)
The objective of the research was to evaluate the organizational culture and its impact on the job satisfaction of the employees of the Aguas de Manta Public Company (EPAM). To this end, three specific objectives were established: carry out a diagnosis of the current situation of the EPAM regarding the organizational culture and its impact on job satisfaction; correlate the variables studied to determine the influence of organizational culture on job satisfaction; and propose strategies that contribute to improving employee job satisfaction. The methodology used consisted of applying an evaluation instrument to EPAM employees, analyzing the data collected using the Spearman correlation method to establish the relationship between the variables. The results revealed a positive and significant correlation between organizational culture and job satisfaction (ρ = 0.35, p = 0.0281), although the strength of this relationship is moderate. Which suggests that as organizational culture improves, employee job satisfaction also increases. The p value less than 0.05 confirms that this result is statistically significant, that is, it is unlikely to be due to chance. It is concluded that the weak correlation between organizational culture and job satisfaction suggests the need for a more in-depth analysis of the factors that affect job satisfaction.